RELIGION: SIGMUND FREUD'S INFANTILE ILLUSIONS AND COLLECTIVE NEUROSIS PERSPECTIVE - Susanto, Susanto; Idris, Saifullah (Ar Raniry : International Journal of Islamic Studies, 2017)
This paper concerns Freud's thoughts on religion. Religion is not only about faith in a great God, but also encompasses the order and discipline of life. Religion involves human relationships, either with God or with others. Freud saw religion as the fulfillment of a childish desire. This can not be separated from his work as a psychologist who produced the concept of psychoanalysis and human sexual stages. Freud disputed the basis of human trust claims by giving three mutually exclusive and holistically unsatisfactory reasons. First, we must trust without demanding proofs; Second, we must believe because our ancestors also believed; And third, we must believe because we have evidence from ancient times. Freud contends that such beliefs are nothing more than an illusion.This paper concerns Freud's thoughts on religion. Religion is not only about faith in a great God, but also encompasses the order and discipline of life. Religion involves human relationships, either with God or with others. Freud saw religion as the fulfillment of a childish desire. This can not be separated from his work as a psychologist who produced the concept of psychoanalysis and human sexual stages. Freud disputed the basis of human trust claims by giving three mutually exclusive and holistically unsatisfactory reasons. First, we must trust without demanding proofs; Second, we must believe because our ancestors also believed; And third, we must believe because we have evidence from ancient times. Freud contends that such beliefs are nothing more than an illusion.Ã‚Â Keywords: Religion, Illusion, Neurosis, Sigmund Freud, Psychoanalysis